UPAYA GURU DALAM MENGINTERNALISASIKAN NILAI – NILAI PENDIDIKAN AGAMA ISLAM BAGI PEMBENTUKAN AKHLAKUL KARIMAH DI SDIT AS SUNNAH KOTA CIREBON - Siti Muzianah (Oasis : Jurnal Ilmiah Kajian Islam, 2017)
Moral or character education is the responsibility of parents as the primary educators and the first of the children and everyone who is close to the students, including policy makers. Moral education in schools is the duty of the principal, teachers of religion, and all citizens of the school. Morals or character taught through methods internalisaai. Engineering education through imitation, habituation, guidance, enforcement of regulations, and motivating and not by way of explaining or discussing. This study discusses the research findings by the title "Master effort in internalize the value - value for the Establishment of Islamic Education akhlakul - Karimah in SDIT As - Sunnah Cirebon City" .. The research method uses qualitative research because the researcher selected according to the type of descriptive explorative research reveals cause and effect, revealing an activity contributes to an achievement. Four keywords that need to be addressed: a scientific way, the data, the purpose and usefulness are logical. Mechanical collection begins orientation phase, the exploration phase and phase to give the check. Data collection techniques presented in this study is the observation, interviews, documentation, and questionnaire data analysis technique that researchers use in this research is holistic and analytical induction. This study presents the results of research conducted in SDIT As - Sunnah Cirebon include (1) Implementation of Islamic religious education to the model of internalization - akhlakul karimah value; (2) factors - factors that affect the implementation of the model of internalization of values - values akhlakul karimah by Islamic religious education teachers, and (3) Successful implementation model of internalizing the values of Islamic religious education with the establishment of akhlakul karimah in SDIT As - Sunnah Cirebon.The results showed ahklakul karimah education an appreciation of the process on a philosophy in depth through two-way interaction without forcing students to do everything he did believed to be true does not deviate from religious norms and norms in society worked well enough, Implementation model of internalization - akhlakul karimah male teachers - men are more dominant than female teachers. Factors - factors that influence that external factors pursued a religious teacher with mengkodisikan environment conducive for tumbuhkembang learners were internal factors with the efforts of internalizing values - values akhlakul karimah in this case the acceptance of female learners are more dominant than men - men. The success of cognitive, affective and psychomotor achieve optimal value with the average - average above 75 from every aspect.Keywords : teacher; internalize; akhlakul; karimah.